A demonstration of wavefront sensing and mirror phasing from the image domain. Issue 1 (8th March 2014) - Pope, Benjamin; Cvetojevic, Nick; Cheetham, Anthony; Martinache, Frantz; Norris, Barnaby; Tuthill, Peter
Abstract: In astronomy and microscopy, distortions in the wavefront affect the dynamic range of a high-contrast imaging system. These aberrations are either imposed by a turbulent medium such as the atmosphere, by static or thermal aberrations in the optical path, or by imperfectly phased subapertures in a segmented mirror. Active and adaptive optics (AO), consisting of a wavefront sensor and a deformable mirror, are employed to address this problem. Nevertheless, the non-common-path between the wavefront sensor and the science camera leads to persistent quasi-static speckles that are difficult to calibrate and which impose a floor on the image contrast. In this paper, we present the first experimental demonstration of a novel wavefront sensor requiring only a minor asymmetric obscuration of the pupil, using the science camera itself to detect high-order wavefront errors from the speckle pattern produced. We apply this to correct errors imposed on a deformable microelectromechanical segmented mirror in a closed loop, restoring a high-quality point spread function and residual wavefront errors of the order of ∼10 nm using 1600 nm light, from a starting point of ∼300 nm in piston and ∼0.3 mrad in tip–tilt. We recommend this as a method for measuring the non-common-path error in AO-equipped ground based telescopes, as well as an approach to phasing difficult segmented mirrors such as on the James Webb Space Telescope primary and as a future direction for extreme AO.